Student z dysfunkcją słuchu w sytuacji kryzysowej związanej z pandemią COVID-19 – analiza indywidualnego przypadku - Gutowska, Anna (Kultura-Społeczeństwo-Edukacja, 2022)
The text, based on the author’s own research, describes the case of a student with a hearing impairment in the context of the effects of the COVID-19 pandemic. The main aim of the research was to answer the question: how did a person with a hearing impairment function during the pandemic and in what dimensions is the pandemic situation a crisis for the examined student with a hearing impairment? The article begins with an introduction to the discussed issues, then takes into account a short description of the studied student and the results of the analysis of the research material obtained with the use of a free-form interview. The article ends with conclusions and a summary. It should be emphasized that the described case can only be treated as a pilot study and preparation of the ground for further explorations of a wider scope.